Potential of antagonist bacteria against Ganoderma boninense and identification of effective key metabolites released - Lau, Wan Koon (2021)
Palm oil is the most consumed vegetable oil in the world. However, the oil palm industry in Southeast Asia is facing greatest threat from basal stem rot (BSR) disease caused by Ganoderma boninense. It causes severe economical loss to the producing countries. Currently there are no methods to effectively detect the disease at early stages of infection; therefore, there is an urgent need to find a practical and environmental-friendly disease control system. Application of biofertiliser with a consortium of biological control agents (BCAs) is widely used in oil palm industry to control BSR disease. In this research, two potential BCAs which were obtained from ACGT Microbial Culture Collection (AMCC): BCA01 (Chromobacterium sp.) and BCA03 (Lysobacter sp.) were selected from 21 isolates via dual culture screening which exhibited 51% and 61% of G. boninense mycelial growth inhibition, respectively. The antagonistic ability was further supported by the characteristic of nitrogen fixation, protease and chitinase production in both BCA01 and BCA03. In addition, the ability to produce siderophore and cellulase enzyme were also determined in BCA03. Additionally, key metabolites involved in the suppression of G. boninense growth were identified to better understand the contributing factor of antagonism. Prominent metabolites detected in BCA01 that could be associated with the biological control activity included mevalonolactone, p-cresol, 4-hydroxycinnamic acid, tiadinil and 13S-hydroperoxy-9Z,11E,15Z-octadecatrienoic acid (13(S)- HpOTrE). These metabolites may be responsible in inhibiting the growth of G. boninense in vivo. However, no potential bioactive metabolites were identified from BCA03 in this experiment. Apart from that, efficacy of the selected BCAs in suppression of G. boninense in oil palm seedlings was conducted using three months-old seedlings. Despite the positive antagonism result obtained in the laboratory, both selected BCAs were not showing similar effect at nursery trial. Treatments with BCA01 and BCA03 recorded disease incidence (DI) percentage as 95% and 93%, respectively demonstrated non-significant infection rate compared to control (90%). Besides that, the expression of cDNAs in oil palm roots at 1, 2, 3, and 4 weeks post inoculation (wpi) with BCA01, BCA03 and G. boninense alone were profiled to further understand the role of BCAs in the induction of defense mechanisms. Real time PCR (qPCR) analysis revealed that cinnamyl alcohol dehydrogenase (CAD), chitinase dan β-1,3-glucanase genes were up-regulated (more than 2-fold) in BCA01 treated roots at 4 wpi compared to negative control (non-infected roots). The result demonstrated that introduction of BCA01 potentially triggered the defense mechanisms of host plants during the interaction with G. boninense at 4 wpi. However, BCA03 did not display any up or down regulations on the three transcripts in this study. From this study, BCA01 was demonstrated as a promising BCA compared to BCA03 in inhibiting the growth of G. boninense by inducing the defense mechanisms of the host plants during infection. The two BCAs could be utilized in developing an environmental-friendly bio-formulation to reduce the usage of synthetic fungicides